Targeting -- Principles and Practice: Technical Guide: Strengthening the Household Food Security and Nutritional Aspects of IFAD Poverty Alleviation Projects: Developing Operational Methodologies for Project Design and Monitoring - Hoddinott, John F. (International Food Policy Research Institute, 1999)
This guide outlines operational methodologies that will improve the targeting of rural development projects. It begins by considering the principles underlying targeting and then considers the practice of targeting.